Ashy dermatosis: A controversial entity - Nandini Chakrabarti; Chandan Chattopadhyay (Wolters Kluwer Medknow Publications, 2012)
We present here the case of a young Indian male with slowly progressive, diffuse darkening of the face, arms, neck, and trunk. The patient was not taking any medication and there was no history of any previous skin disease and the mucous membrane was not involved. These findings are consistent with a diagnosis for ashy dermatosis of unknown etiology.